2008
DOI: 10.1002/ijc.23407
|View full text |Cite
|
Sign up to set email alerts
|

The DNA demethylating agent 5‐aza‐2′‐deoxycytidine activates NY‐ESO‐1 antigenicity in orthotopic human glioma

Abstract: Cancer/testis antigens (CTAs) are considered to be suitable targets for the immunotherapy of human malignancies. It has been demonstrated that in a variety of tumors, the expression of certain CTAs is activated via the demethylation of their promoter CpG islands. In our study, we have shown that while the composite expression of 13 CTAs in 30 human glioma specimens and newly established cell lines from the Japanese population was nearly imperceptible, the DNA-demethylating agent 5-aza-2 0 -deoxycytidine (5-aza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 42 publications
4
67
0
Order By: Relevance
“…One way to bypass this lack of identified antigens for MPM is to force tumour cells to express tumour-associated antigens (TAAs). With the aim of favouring TAA expression, it has been shown that hypomethylating drugs and/or HDAC inhibitors, in addition to restoring a normal epigenetic status in cancer cells, can also induce tumour antigen expression [17][18][19][20][21].…”
Section: Alignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%
“…One way to bypass this lack of identified antigens for MPM is to force tumour cells to express tumour-associated antigens (TAAs). With the aim of favouring TAA expression, it has been shown that hypomethylating drugs and/or HDAC inhibitors, in addition to restoring a normal epigenetic status in cancer cells, can also induce tumour antigen expression [17][18][19][20][21].…”
Section: Alignant Pleural Mesothelioma (Mpm)mentioning
confidence: 99%
“…Female 7-week-old mice nonobese diabetic/severe combined immunodeficiency disease (NOD/SCID) were used as described previously. 32 All mice were purchased from Charles River Lavoratories, Osaka, Japan. Mice were anaesthetized with an intraperitoneal injection of pentobarbital (60-70 mg/ kg body weight).…”
Section: Cell Migration and Invasion Assaymentioning
confidence: 99%
“…We stereotactically injected 0316-GICs (1 × 10 5 cells) resuspended in 5 μL of PBS into 5-to 6-wk-old nonobese diabetic/severe combined immunodeficient female mice (SLC, Shizuoka, Japan) as described previously (40). IFN-β (2 × 10 5 IU/animal) was given i.p.…”
Section: Intracranial Glioma Xenograft and Ifn-β Treatmentmentioning
confidence: 99%